Hubungan Tingkat Pengetahuan Lansia Tentang Covid-19 dengan Gangguan Psikologis Lansia di Masa Pandemik - Esti Nur Janah; Slamet Riyadi; Raden Nur Abdurakhman (Journal of Bionursing, 2021)
Most patients infected with SARS-CoV-2 show respiratory symptoms such as fever, coughing, sneezing, and shortness of breath. COVID-19 patients with severe pneumonia are characterized by fever, plus one of the symptoms in geriatric patients can appear atypical symptoms. The Central Statistics Agency projects that by 2045 Indonesia will have around 63.31 million elderly or nearly 20 percent of the population. In fact, the UN projection also states that the percentage of Indonesian elderly will reach 25 percent in 2050 or around 74 million elderly. The purpose of this study was to determine the relationship between knowledge about Covid-19 and the psychological problems of the elderly during the pandemic in Paguyangan Village, Paguyangan District, Brebes Regency 2020. This research is a descriptive study with a cross sectional approach. The research design used was descriptive analytic with cross sectional approach. The population in this study were 711 elderly people aged 60 years or more in Paguyangan Village, Paguyangan District, Brebes Regency. The majority of respondents had a moderate level of knowledge, namely 56 respondents or 62.2%. The results of this study indicate a significant relationship between knowledge and anxiety levels with a p value of 0.000 with a positive correlation, which means that the higher the knowledge is followed by the higher the level of anxiety with a correlation strength of 0.643 (strong).